MEMAHAMI PASAR KUE TRADISIONAL DJAJE MELALUI ANALISIS STP: SEGMENTATION, TARGETING, POSITIONING - Nurul Baikhaq (Yayasan Grace Berkat Anugerah, 2025)
In this study, the digital marketing strategy uses STP (Segmentation, Targeting, Positioning) analysis by determining target consumers such as those aged 22-60 years who are in the Denpasar and surrounding areas and have an interest in religious events such as weddings, celebrations, and others. Implementation of the digital marketing strategy by implementing it on existing digital platforms such as Facebook, Instagram, WhatsApp Business, website, and Google Business Profile. Another strategy used is to advertise on Facebook and Instagram as well as websites. In addition to using the online method, offline also adds the number of resellers. The results of the research conducted after applying STP (Segmentation, Positioning, Targeting) analysis on the various platforms used, namely the increasing number of sales from October 2021 to March 2022.